2008
DOI: 10.1007/s00894-008-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

The decomposition of α-aminophosphine oxides to phosphonic acid derivatives (PIII)

Abstract: Aminophosphine oxides and aminophosphonates are, in general, very stable compounds. However, following phosphorus-carbon bond cleavage in aqueous acidic media these compounds sometimes decompose to phosphonic acids derivatives (P(III)). Despite some controversy in the literature, careful analysis supported by theoretical studies leads to the conclusion that decomposition to P(III) derivatives proceeds via an elimination reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This study confirmed that a three-step process including amino-group protonation, proton transfer through a hydrogen-oxygen bond NH•••O(P), 43 and P-C bond cleavage, leading to a protonated imine and derivatives of H-phosphonate is the most probable mechanism. 6,27,28,43,44 It should be noted that for N-alkyl aminophosphonates the decomposition is not observed as the amine nitrogen in this case is protonated and formation of imine (leaving group) is prevented. Lowering the basicity of the amine as is the case in the N-benzhydryl derivative, again facilitates the elimination process 47 Decomposition to P V .…”
Section: Thermodynamic Studiessupporting
confidence: 76%
See 2 more Smart Citations
“…This study confirmed that a three-step process including amino-group protonation, proton transfer through a hydrogen-oxygen bond NH•••O(P), 43 and P-C bond cleavage, leading to a protonated imine and derivatives of H-phosphonate is the most probable mechanism. 6,27,28,43,44 It should be noted that for N-alkyl aminophosphonates the decomposition is not observed as the amine nitrogen in this case is protonated and formation of imine (leaving group) is prevented. Lowering the basicity of the amine as is the case in the N-benzhydryl derivative, again facilitates the elimination process 47 Decomposition to P V .…”
Section: Thermodynamic Studiessupporting
confidence: 76%
“…This conclusion about the mechanism is strongly supported by the measured entropy of activation and by theoretical calculations. 37,43,44 The decomposition to P V derivatives in water was proposed to proceed via nucleophilic substitution, which is typical of compounds containing a tetracoordinated phosphoryl group. Our results -the steric influence on the reaction rate, the low entropy of activation, k H /k D typical for bimolecular prototropic reactions, the kinetic studies and the dependence of water concentration on reaction rate -all indicate that nucleophilic substitution or at least advanced formation of a bond with the nucleophile, occur in the transition state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete hydrolysis of the diethyl ester of phosphonates M-1 was achieved using trimethylsilyl bromide (TMSBr) according to the approach described previously. Treatment of the starting porphyrin Ga-1b , which was chosen as a model compound, with an excess of TMSBr in dry dichloromethane (CH 2 Cl 2 ) resulted in the formation of Ga-5b bearing a bromine atom as an axial ligand (see the details in the SI, X-ray structure part). C–P bond cleavage has already been observed for diethyl or diphenyl phosphonates under acidic conditions, and possible mechanistic pathways were postulated, but the detailed mechanism still requires further investigations.…”
Section: Resultsmentioning
confidence: 99%